A Silicon‐Heteroaromatic System as Photosensitizer for Light‐Driven Hydrogen Production by Hydrogenase Mimics1. Issue 25 (4th July 2013) - Goy, Roman; Apfel, Ulf‐Peter; Elleouet, Catherine; Escudero, Daniel; Elstner, Martin; Görls, Helmar; Talarmin, Jean; Schollhammer, Philippe; González, Leticia; Weigand, Wolfgang
Abstract: The utilization of light and inexpensive catalysts to afford hydrogen represents a huge challenge. Following our interest in silicon‐containing [FeFe]‐hydrogenase ([FeFe]‐H2 ase) mimics, we report a new model approach for a photocatalytic [FeFe]‐H2 ase mimic1, which contains a 1‐silafluorene unit as a photosensitizer. Thereby, the photoactive ligand is linked to the [2Fe2S] cluster through S–CH2 –Si bridges. Photochemical H2 evolution experiments were performed and revealed a turnover number (TON) of 29. This is the highest reported photocatalytic efficiency for an [FeFe]‐H2 ase model complex in which the photosensitizer is covalently linked to the catalytic center. Abstract : We report a viable synthetic pathway for the construction of a new photoactive model of the [FeFe]‐hydrogenase ([FeFe]‐H2 ase) active site with a dithiolate bridge and 1‐silafluorene as a photosensitizer. The [FeFe]‐H2 ase mimic represents a very compact, easily accessible, and inexpensive photocatalyst for hydrogen generation.